2000
DOI: 10.5326/15473317-36-2-125
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of cardiomyopathy in the Irish wolfhound: a clinical study of 500 dogs

Abstract: The prevalence of cardiomyopathy in Irish wolfhounds was evaluated by retrospective review of the results of cardiovascular examinations carried out in 500 dogs presented for veterinary services at the author's practice. Abnormalities were found in 209 (41.8%) of the dogs examined. Dilated cardiomyopathy (DCM) was diagnosed in 121 (24.2%) of the dogs and was accompanied by atrial fibrillation in 106 dogs. Seventeen dogs were suffering from advanced congestive heart failure (CHF), and 55 dogs were suffering fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
2
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 9 publications
(11 reference statements)
6
82
2
6
Order By: Relevance
“…Contributing to its' small gene pool is the fact that the breed suffered a severe bottleneck in the mid 1800's, such that Irish Wolfhound were considered by many to be extinct. The breed is at high risk for dilated cardiomyopathy, with the disorder possibly affecting as much as one-third of the population (www.iwclubofamerica.com) 62 . Once the disease gene is identified, a strict screening and removal policy that would restrict dogs carrying even one disease allele from producing registered dogs would likely destabilize the gene pool, resulting in many new recessive disorders "popping-up" in the breed.…”
Section: Developmentmentioning
confidence: 99%
“…Contributing to its' small gene pool is the fact that the breed suffered a severe bottleneck in the mid 1800's, such that Irish Wolfhound were considered by many to be extinct. The breed is at high risk for dilated cardiomyopathy, with the disorder possibly affecting as much as one-third of the population (www.iwclubofamerica.com) 62 . Once the disease gene is identified, a strict screening and removal policy that would restrict dogs carrying even one disease allele from producing registered dogs would likely destabilize the gene pool, resulting in many new recessive disorders "popping-up" in the breed.…”
Section: Developmentmentioning
confidence: 99%
“…The mean age at death for males and females that had survived their first year of life was 4.95 + 0.94 years and 6.59 + 0.95 years respectively. There was a high mortality in the first year of life, only 61.29% of males and 72.92% of females born alive reaching one year.of age. Given that effective vaccines and antibiotics were not available in veterinary science at the time, it is likely that infectious diseases were an important part of these early losses.…”
Section: Irish Wolfhound Lifespanmentioning
confidence: 99%
“…It was suggested that an autosomal dominant pattern of inheritance would best fit the observed distribution (17,72). The most recent study (9) found that a mixed inheritance model with polygenic effects and a segregating major gene explained the observed DCM cases best.…”
Section: Irish Wolfhound Lifespanmentioning
confidence: 99%
See 1 more Smart Citation
“…The Irish Wolfhound (IW) breed has been noted for its high prevalence of dilated cardiomyopathy (DCM), atrial fibrillation (AF), or both 1, 2, 3, 4, 54, 5, 6 In 1 large study of 1,038 IW dogs prospectively screened between 1990–2004, approximately 29% were affected,7 and in selected populations of IW dogs, AF has been reported in up to 21% of screened animals 4, 5, 6, 7, 4, 7. Moreover, AF may develop before structural or functional changes become apparent, and some affected dogs may progress to DCM and congestive heart failure (CHF) 6, 7, 8…”
mentioning
confidence: 99%